MODEL PENGEMBANGAN KARAKTER SANTRI DI PESANTREN PERSIS 67 BENDA TASIKMALAYA JAWA BARAT - moh. dulkiah (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
This study aims to describe the model of character development of santri in Pesantren Persis 67 Benda Tasikmalaya West Java. Data collection method used in field research with the qualitative approach with observation data and in-depth interview. The results showed that: First, character development of santri lies in the process of teaching, habituation, and enforcement of rules. Secondly, the teaching model provides development not only in the curriculum that combines the curriculum content of the ministry of religions, the curriculum content of the ministries of education and culture, and the content of the local curriculum, but also contains principles that the teacher (ustadz) considers in curriculum development, namely: the proximity of the relationship between the learning material and the occurring phenomenon), the principle of flexibility (the developed curriculum must have the space for freedom of action, choosing the educational program, and the flexibility in the development of the learning program), the efficiency principle (effort, cost, time, which is used in the learning process must be strict), the principle of effectiveness (curriculum planning can be achieved in accordance with predetermined desires), the principle of continuity (curriculum development shows the relationship between education level, type of education, education program and field of study). Third, habituation is oriented to apply the value of independence and the value of responsibility. Fourth, enforcement of rules is implemented not to give physical sanctions, but rather more motivational.